464 Alternative RNA Splicing Changes Underlie Meningioma DNA Methylation Groups. (April 2023) - Leclair, Nathan; Choudhury, Abrar; Magill, Stephen; Shen, Erica; Bulsara, Ketan R.; Raleigh, David R.; Anczukow, Olga
Abstract : INTRODUCTION: Meningiomas are the most common primary intracranial tumor. They are associated with genetic mutations found across broad epigenetic or transcriptomic groups. Alternative RNA splicing (AS) is a critical step in gene expression that involves the differential inclusion of sequences into the mature mRNA. Dysregulation of AS is a hallmark of human tumors, but its contributions to meningioma tumorigenesis are incompletely understood. In particular, whether meningioma DNA-methylation groups are associated with specific downstream changes in AS is unknown. METHODS: AS events from 184 meningiomas were characterized using rMATS, a computational tool that quantifies percent splicing event inclusion (PSI) from short-read RNA-sequencing. Differential gene expression was quantified using DESeq2. RESULTS: Our analysis revealed 135 differentially spliced events in Immune-enriched vs. Hypermitotic meningiomas, 126 events in Immune-enriched vs. Merlin-intact meningiomas, and 185 events in Merlin-intact vs. Hypermitotic meningiomas. Hierarchical clustering of samples based on differential splicing events separated Hypermitotic from Merlin-intact and Immune-enriched meningiomas. The proto-oncogenes Misshapen-like Kinase 1 (MINK1) and Nuclear Auto-antigenic Sperm Protein (NASP) were differentially spliced across WHO grades, DNA methylation groups, and in primary vs. recurrent meningiomas and correlated with recurrence free survival. Differential gene expression analysis revealed alterations in the expression of several splicing factors across methylation groups, including those involved in tumorigenesis (MEX3A, SNRPE, SRSF5). CONCLUSIONS: AS promotes differential isoform expression across clinically important DNA-methylation groups of meningiomas. Our analyses capture a splicing signature that correlates with meningioma aggressiveness, identifies prognostic splicing events in known human proto-oncogenes (MINK1, NASP), and uncovers their potential upstream regulators. Validation of how these events impact meningioma tumorigenesis may allow for the development of novel diagnostic tests and therapies targeting AS.